Susan Kent (ed.): Domestic Architecture and the Use of Space - An Interdisciplinary Cross-Cultural Study - Westman, Bror (Tidsskriftet Antropologi, 2019)
Susan Kent (ed.): Domestic Architecture and the Use of Space - An Interdisciplinary Cross-Cultural Study Anmeldes af Bror Westman